PENGARUH NILAI HEDONIS DAN UTILITARIAN PADA WORD OF MOUTH DENGAN KEPUASAN KONSUMEN SEBAGAI PEMEDIASI - Muhammad Mathori; Uswatun Chasanah (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2021)
This study examines the direct relationship between hedonic value and utilitarian value variables with customer satisfaction and word of mouth (WOM). The respondents of this study were 115 undergraduate and postgraduate students at private universities in Yogyakarta. Data processing was performed with Smart PLS 3.2.9, the results show that there is a direct relationship between hedonic value and utilitarian value variables on customer satisfaction. The direct relationship between hedonic value and utilitarian value variables with WOM is not proven. The indirect relationship between hedonic value and utilitarian value variables in WOM with customer satisfaction as a proven mediator, while customer satisfaction is a variable predictor as an antecedent of WOM.